2022
DOI: 10.1007/s12613-021-2323-1
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress of efficient utilization of titanium-bearing blast furnace slag

Abstract: Titanium-bearing blast furnace slag (BFS) has valuable compositions and potential environmental hazardousness. Thus, developing efficient and green approaches to utilize BFS is highly desired for resource economization and environmental protection. In the past decades, many attempts have been adopted to reuse BFS efficiently, and significant advances in understanding the fundamental features and the development of efficient approaches have been achieved. This review provides a comprehensive overview of the lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 48 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…12 Due to the preciousness of titanium resources, most of the high-titanium contained slag is treated by titanium extraction or preparation of titanium alloys. 13,14 The results of some studies have shown that when the content of TiO 2 in slag is greater than 4 wt%, the activity and strength of cement will be significantly reduced. Hence, almost all low-titanium contained slag can be used as ordinary BFS in construction materials without special processing.…”
Section: Introductionmentioning
confidence: 99%
“…12 Due to the preciousness of titanium resources, most of the high-titanium contained slag is treated by titanium extraction or preparation of titanium alloys. 13,14 The results of some studies have shown that when the content of TiO 2 in slag is greater than 4 wt%, the activity and strength of cement will be significantly reduced. Hence, almost all low-titanium contained slag can be used as ordinary BFS in construction materials without special processing.…”
Section: Introductionmentioning
confidence: 99%
“…Over 3-million tons of Ti-bearing blast furnace slag (TBBFS) are generated annually when vanadium-titanium magnetite is melted for iron production [2,3]. The inappropriate disposal of TBBFS cannot only be hazardous to the environment but also lead to a potential waste of titanium resources [4]. Recently, the conversion of TBBFS into photocatalytic materials (TiO 2 , CaTiO 3 ) has garnered significant attention and can be achieved through alkali fusion and acid leaching [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…TBBFS has the advantage of high Ti content and utilizes Ti components. Previous studies have proven that implementing slag modification combined with selective crystallization allows for the enrichment of Ti in the form of a perovskite phase, while the remaining components exist in an amorphous state [4,17]. Based on this, we proposed a facile and straightforward methodology for manufacturing photocatalytic porous geopolymers from TBBFS.…”
Section: Introductionmentioning
confidence: 99%
“…The main purpose of hydrometallurgy for Ti-bearing blast furnace slag is the separation of valuable metals. 20 Therefore, in hydrometallurgy, the key is for the target components to dissolve as much as possible in the solution. For air-cooled slag, the high crystallization degree makes it difficult for most metals to dissolve, and theoretical research on the leaching process is relatively poor.…”
Section: Introductionmentioning
confidence: 99%